Extending message-oriented middleware - Estévez, Elsa Clara (2005)
Different types of middleware exist to facilitate the integration of software running on heterogeneous computing platforms. Message Oriented Middleware (MOM), for instance, enables the interaction between heterogeneous applications by exchanging packets of structured data (messages) through communication channels. The core responsibility of a MOM is asynchronous delivery of messages from senders to receivers, as well as management of the corresponding message queues. However, realistic software applications need many more messaging functions, for instance functions to enable auditing, encryption, tracking and transformation of messages. Such functions should be clearly provided by the underlying MOM and not implemented and re-implemented by applications themselves. In this paper, we present an approach for extending the core functionality of a MOM. In particular, we investigate how such extensions can be configured and combined, to ensure correct delivery of messages.